Building assessment in Brazil: from environmental to sustainability assessment - Silva, Vanessa Gomes da (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
Governmental agencies, research institutions and private sector worldwide have largely encouraged the development of research concerned with the reduction of the environmental impacts of buildings. The concept of life cycle analysis has supported the development of methodologies for environmental assessment of buildings that emerged in the 90’s as part of the strategies for the attainment of local environmental targets set at the ECO’92. Each European country, as well as the United States, Canada, Australia, Japan and Hong Kong, has its own assessment system. All of them deal exclusively with the environmental dimension of building sustainability. This paper presents and briefly compares the main initiatives on environmental assessment and rating systems, emphasizing the inadequacy of simply importing existing methods based on their success in countries with latitudes, social, economic and environmental conditions far different from those in Brazil. Finally, it discusses the expectations regarding the participation of Brazil in the Green Building Challenge, as well as the strategies to develop research in this field in this country.